Basal forebrain and prelimbic cortex connectivity is related to behavioral response in an attention task - Faezeh Tashakori-Sabzevar; Robert G.K. Munn; David K. Bilkey; Ryan D. Ward (iScience, 2024)
Summary: The basal forebrain (BF) is critical for the motivational recruitment of attention in response to reward-related cues. This finding is consistent with a role for the BF in encoding and transmitting motivational salience and readying prefrontal circuits for further attentional processing. We recorded local field potentials to determine connectivity between prelimbic cortex (PrL) and BF during the modulation of attention by reward-related cues. We find that theta and gamma power are robustly associated with behavior. Power in both bands is significantly lower during trials in which an incorrect behavioral response is made. We find strong coherence during responses that are significantly stronger when a correct response is made. We show that information flow is largely monodirectional from BF to and is strongest when correct responses are made. These experiments demonstrate that connectivity between BF and the PrL increases during periods of increased motivational recruitment of attentional resources.